Creating Spaces for Transdisciplinary Learning (CreST) - (:unkn) unknown (My University, 2025)
In today's world, putting sustainable development into practice has become one of the most important tasks of society. Since this task has consequences for future generations, it is necessary to involve students, teachers, and their places of learning. The CreST project will create a new course – the "CreST Workshop" – through a partnership between the University of Geneva, the University of Neuchâtel, and the Geneva University of applied sciences technology, architecture and landscape (hepia). An interdisciplinary team of professors and senior lecturers will teach CreST workshops annually. One of the main goals of the workshops is to support concrete sustainable development processes such as regional development and planning in agglomerations or transboundary environments. Therefore, students will interact in groups with stakeholders to jointly develop questions, approaches, and outputs. Throughout the project, the workshops will be tested, evaluated, and refined, using feedback from all involved. Moreover, the workshop experiences will help strengthen the role of sustainable development in institutions of higher learning, public administration, civil society, and the private sector. Finally, the CreST team will actively participate in national and international networks and events to present its approaches and learn from others.
Keywords: University of Geneva; University of Neuchâtel; Geneva University of applied sciences technology; architecture and landscape hepia; master course/workshop; transdisciplinary learning; regional development and planning